2015
DOI: 10.1631/jzus.b1500147
|View full text |Cite
|
Sign up to set email alerts
|

Submerged fermentation production and characterization of intracellular triterpenoids from Ganoderma lucidum using HPLC-ESI-MS

Abstract: Abstract:As the main bioactive metabolites of Ganoderma lucidum, triterpenoids have various pharmacological effects. In this paper, the nutritional requirements and culture conditions of a submerged culture of G. lucidum were optimized using the response surface methodology; maximum mycelia biomass and intracellular triterpenoid production reached 1.87 g/100 ml and 93.21 mg/100 ml, respectively, for a culture consisting of wort 4.10% (0.041 g/ml) and yeast extract 1.89% (0.0189 g/ml), pH 5.40. For the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…However, Gorlenko et al (1959) established that pH values of 6.0-7.0 are ideal for increased mycelial mass in A. musiformis and A. conoides. Cui et al found that mycelial biomass and triterpenoid production in Ganoderma lucidum reached a maximum at pH 5.5, and declined rapidly outside the pH range of 4.5-6.5 (Cui et al 2015). This evidence indicates that some fungi prefer to grow in weakly acidic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Gorlenko et al (1959) established that pH values of 6.0-7.0 are ideal for increased mycelial mass in A. musiformis and A. conoides. Cui et al found that mycelial biomass and triterpenoid production in Ganoderma lucidum reached a maximum at pH 5.5, and declined rapidly outside the pH range of 4.5-6.5 (Cui et al 2015). This evidence indicates that some fungi prefer to grow in weakly acidic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The most suitable concentrations of corn powder and soybean meal were 15 g/L and 6 g/L, respectively, in the present study. Further increase of the concentrations of these two substances was found to be unfavorable for mycelial growth and polysaccharide production, probably due to excessively high osmotic pressure caused by nutrients at high concentrations (Cui et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fermentation culture contained (g/L): wort 41, peptone 18.9, KH 2 PO 4 3, MgSO 4 1.5, and VB 1 0.05 (pH 5.4) (Cui et al, 2015).…”
Section: Liquid Cultivation Of Ganoderma Lucidummentioning
confidence: 99%
“…However, when more than one response must be optimized, it is necessary to use the so-called desirability functions [4]. RSM was often utilized to optimize different bioprocesses such as anaerobic digestion [5] and productions of bioethanol [6], lactic acid [7], triterpenoids [8], and biodiesel [9], among others. This methodology has also been successfully applied to xylose-to-xylitol bioconversion by the yeasts Candida tropicalis [10], Pachysolen tannophilus [11], Candida guilliermondii [12], and Debaryomyces hansenii [13].…”
Section: Introductionmentioning
confidence: 99%